Jiedutongluotiaogan Formula Improves Pancreatic Dysfunction in db/db Mice through Modulating the Gut Microbiota-Short Chain Fatty Acids-NLR Family, Pyrin Domain–Containing Protein 3 Inflammasome - Jin-Li Luo; Wen-Qi Jin; Li Wang; Qi Zhang; Yu Wang; Cui Wu; Yue Qu; Yu-Ting Peng; Li-Wei Sun; Chun-Li Piao (World Journal of Traditional Chinese Medicine)
Objective: Disturbance of gut microbiota plays an essential role in metabolic diseases, such as diabetes. Jiedutongluotiaogan formula (JTTF) was designed to meliorate the symptoms of type 2 diabetes. Materials and Methods: In this study, we used a db/db mouse model to determine the possible relationship between the imbalance of the intestinal flora and islet β cells. JTTF was orally administered at doses of 5.0 g·kg − 1·d − 1 in diabetic mice. Histopathological analyses, ELISA, metabolomics analysis, 16S rRNA analysis, high-performance liquid chromatography-mass spectrometry, and western blot were performed to identify the therapeutic effects and mechanisms of JTTF in treating diabetes. Results: JTTF intervention significantly improved glycolipid metabolism and gut flora diversity in db/db mice. JTTF increased the abundance of Lachnospiraceae, Oscillibacter, Lachnoclostridium, and Roseburia in db/db mice and the content of short-chain fatty acids. Furthermore, a significant reduction in inflammatory factors, recombinant NLR family, pyrin domain–containing protein 3 (NLRP3), apoptosis-associated speck-like protein containing a caspase recruitment domain (ASC), and CASPASE-1 serum protein levels, was also observed in the pancreas. Conclusion: The effects of JTTF on glycolipid metabolism disorder may be attributed to its ability to modulate the gut microbiota, limit excessive lipopolysaccharide release, and inhibit NLRP3 activation to an abnormally high level, which might be one of the important mechanisms of JTTF in treating diabetes.